Impact of School Environment on Students Behaviour: A Case of Public and Private Schools - Rind, Zain ul abdin; Khaskhali, Shaista; Mubeen, Aneeta (Annals of Human and Social Sciences, 2023)
School Environment refers to the interactions inside a school community and are shaped by the learning environment’s structural, individual, and functional elements that give schools their unique character. The educational setting plays a significant role in assessing the well-being of students. The purpose of this study was to investigate behavioural, and physical school environment in both public and private schools and to find out the relationship between school environment and students behavior. Descriptive research design was used in this study. The research created a survey questionnaire with a three-point Likert scale that included questions about the academic environment, motivation, and free-factor behaviour. Both public and private schools in District Matiari comprised the study’s population. Three hundred eighty-seven randomly chosen schools from the public and private sectors made up the sample. The analysis showed that private-sector classrooms had considerably better learning environments than public-sector ones. However, there was no statistically significant difference between the two sectors’ behaviour, academic performance, and school climate. The cumulative mean indicated that both sectors needed to enhance one area of the educational setting. It is recommended that the public school environment be enhanced with the behavioural and physical environment and regular motivational speakers and events be hosted in schools.